Analisis Biaya Yang Hilang Dari Sisa Makanan Pasien Di Rumah Sakit Umum Daerah Kota Mataram Yang Mendapatkan Makanan Biasa - Baiqwinda Sari Febri; AASP Chandradewi; Irianto Irianto; Reni Sofiyatin (Poltekkes Kemenkes Mataram, 2018)
Background. The organization of food is one form of hospital nutrition service. The success of the food system can be attributed to food scraps. The rest of the patient's food causes the missing costs and impacts on the budget used. Research Methods. The organization of food is one form of hospital nutrition service. The success of the food system can be attributed to food scraps. The rest of the patient's food causes the missing costs and impacts on the budget used. Research Result. The results of this study show the results of multiple regression logistic tests that have a significant value of 0.068 (p> 0.05). This means that there is no influence of age, sex, type of illness and taste of food against the cost of missing ordinary food scraps. Conclusion. Age, sex, disease type and food taste assessment contribute 13.2% to the lost cost of food scraps.